PAJAK DAN ASPEK HUKUM PERDATA - Hulman Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Taxes can be studied or analyzed from various disciplines, including law. Tax talks from the point of view of law are called tax laws. Civil law aspects, are a big part of tax law. Tax is an engagement. Many institutions con- tained in binding law as regulated in book III of the Civil Code are used in tax law. Keyword : taxes; tax laws; regulatation tax.